State-of-the-art look at premature ventricular complex diagnosis and management: Key messages for practitioners from the American College of Cardiology Electrophysiology Council - Erdi Babayiğit; Taner Ulus; Bülent Görenek (KARE Publishing, 2020)
Premature ventricular complexes (PVCs) are one of the most common arrhythmias seen in daily practice. Although PVCs are generally considered benign, they can lead to the development of cardiomyopathy and, rarely, can be associated with sudden cardiac death. Recently, the American College of Cardiology Electrophysiology Council published a state-of-the-art review on PVCs to provide diagnostic and therapeutic considerations for clinical practice. Presented are some important points about the diagnosis, approach, and treatment of PVCs.